Therapy With Different Dose Regimens of Rituximab in Patients With Active Moderate-To-Severe Graves’ Orbitopathy - Campi, Irene; Vannucchi, Guia; Muller, Ilaria; Lazzaroni, Elisa; Currò, Nicola; Dainese, Martina; Montacchini, Benedetta; Covelli, Danila; Guastella, Claudio; Pignataro, Lorenzo; Fugazzola, Laura; Arosio, Maura; et al. (Frontiers in Endocrinology, 2022)
Background: Immunosuppressive therapy of Graves’ orbitopathy (GO) is indicated during the active phase of disease. Intravenous steroids (IVGC) are effective in about 70% of patients, although unresponsiveness or relapse are observed. In previous studies, rituximab (RTX) has been shown to be effective in inactivating moderate-to-severe GO when used early in the disease, but its optimal dosage has never been studied in randomized clinical trials. Aim of this study was to compare the efficacy and safety of different doses of RTX, based on a post-hoc analysis of two open label studies and one prospective trial randomized to IVGC. Methods: of 40 patients (35 women, 5 men), with active moderate-to-severe GO treated with RTX, 14 received a single dose of 100 mg (Group 1), 15 a single dose of 500 mg (Group 2) and 11 two 1000 mg doses, administered one week apart (Group 3). Thyroid function, TSH-receptor antibodies (TRAb) and peripheral CD19+ cells were measured. Primary endpoint was disease inactivation, measured as a decrease of the Clinical Activity Score (CAS) of at least two points. Secondary endpoints were improvement of proptosis, diplopia, quality of life and safety. Results: Baseline CAS decreased significantly in all groups (P<0.0001), independently of GO duration or whether patients had newly occurring or relapsing GO after IVGC. Proptosis did not significantly change. There was an inverse correlation between the Gorman score for diplopia and RTX dose (P<0.01). The appearance score of the GO-QoL improved in Group 1 (P=0.015), and the visual function score, in Group 2 (P=0.04). A reduction of serum TRAb was observed in Group 1 (P=0.002) and Group 2 (P<0.0002), but not in Group 3. CD19+ cell decreased in all groups (P<0.01), independently of the dose. Conclusions: We studied the optimal dosage of RTX in the treatment of active moderate-to-severe GO. In this analysis, we considered the efficacy of RTX in inactivating GO, in changing its natural course, its effect on disease severity and on the patients’ quality of life. Based on our clinical findings, and balancing the cost of therapy, a single 500 mg dose regimen is suggested in the majority of patients.